2023
DOI: 10.1093/plphys/kiad174
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-binding protein OsANN1 regulates rice blast disease resistance by inactivating jasmonic acid signaling

Abstract: Rice blast, caused by the fungal pathogen Magnaporthe oryzae, is one of the most devastating diseases in rice (Oryza sativa L.). Plant annexins are calcium- and lipid-binding proteins that have multiple functions; however, the biological roles of annexins in plant disease resistance remain unknown. Here, we report a rice annexin gene, OsANN1 (Rice annexin 1), that was induced by M. oryzae infection and negatively regulated blast disease resistance in rice. By yeast two-hybrid screening, we found that OsANN1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Annexins belong to a multifunctional protein family that exists in plants, animals and fungi [10]. Recent evidence has shown that plant annexins play critical roles in regulating abiotic and biotic stresses [19,21,25,38]. Our previous study showed that OsANN3 enhances tolerance to drought stress by modulating ABAdependent stress response pathways in rice [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Annexins belong to a multifunctional protein family that exists in plants, animals and fungi [10]. Recent evidence has shown that plant annexins play critical roles in regulating abiotic and biotic stresses [19,21,25,38]. Our previous study showed that OsANN3 enhances tolerance to drought stress by modulating ABAdependent stress response pathways in rice [26].…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, OsANN1 interacts with OsHAN1 and promotes JA-Ile to exhibit an inactive form. Upon pathogen infection, OsANN1 and HAN1 are separated, leading to HAN1 degradation and JA-Ile accumulation, thus promoting disease resistance [25]. The overexpression of OsANN3 significantly increases drought tolerance by regulating ABA-dependent stress response pathways [26].…”
Section: Introductionmentioning
confidence: 99%